Application of Buteyko Breathing Exercise Technique to Stabilize Respiratory Rate in Bronchial Asthma Patients (JONAH : Journal of Nursing and Homecare, 2024)
One of the diseases that can cause obstructions in the respiratory tract is BronchialAsthma. Asthma makes the airways in the lungs narrow due to inflammation and tightening of the muscles around the airways. Inflammation can cause cells in the respiratory tract to produce a lot of secret, as a result air flow can be obstructed in the respiratory tract which causes shortness of breath making it difficult to breathe.When asthmatics feel shortness of breath, there will be an increase in respiratory frequency and a decrease in oxygen saturation. Non-pharmacological therapy methods in the form of breathing techniques can be performed on asthma patients,one of which is the Buteyko Breathing Exercise technique. Buteyko BreathingExercise technique combines nasal breathing, diaphragm and pause control. Thepurpose of this study was to determine the stability of Respiratory Rate in patientswith Bronchial Asthma after applying Buteyko Breathing Exercise Technique. Thisresearch is a descriptive case study with 2 research subjects and was conducted inMay 2023. This study uses interview, observation and physical examinationtechniques in data collection with previously prepared instruments. Data ispresented in the form of narratives and tables. The results show that there is a change in Respiratory Rate to be stable in both subjects, with the mode value ofRespiratory Rate in the first subject is 18 x/min and the second subject is 20 x/min.